Computational Tools for the Integrated Design of Advanced Nuclear Reactors. (August 2017) - Touran, Nicholas W.; Gilleland, John; Malmgren, Graham T.; Whitmer, Charles; Gates, William H.
Abstract: Advanced nuclear reactors offer safe, clean, and reliable energy at the global scale. The development of such devices relies heavily upon computational models, from the pre-conceptual stages through detailed design, licensing, and operation. An integrated reactor modeling framework that enables seamless communication, coupling, automation, and continuous development brings significant new capabilities and efficiencies to the practice of reactor design. In such a system, key performance metrics (e.g., optimal fuel management, peak cladding temperature in design-basis accidents, levelized cost of electricity) can be explicitly linked to design inputs (e.g., assembly duct thickness, tolerances), enabling an exceptional level of design consistency. Coupled with high-performance computing, thousands of integrated cases can be executed simultaneously to analyze the full system, perform complete sensitivity studies, and efficiently and robustly evaluate various design tradeoffs. TerraPower has developed such a tool—the Advanced Reactor Modeling Interface (ARMI) code system—and has deployed it to support the TerraPower Traveling Wave Reactor design and other innovative energy products currently under development. The ARMI code system employs pre-existing tools with strong pedigrees alongside many new physics and data management modules necessary for innovative design. Verification and validation against previous and new physical measurements, which remain an essential element of any sound design, are being carried out. This paper summarizes the integrated core engineering tools and practices in production at TerraPower.